Bevacizumab impairs oxidative energy metabolism and shows antitumoral effects in recurrent glioblastomas: a (31)P/(1)H MRSI and quantitative magnetic resonance imaging study - Hattingen, Elke (Oxford University Press, 2011)
Bevacizumab shows unprecedented rates of response in recurrent glioblastomas (GBM), but the detailed mechanisms are still unclear. We employed in vivo magnetic resonance spectroscopic imaging (MRSI) and quantitative magnetic resonance imaging to investigate whether bevacizumab alters oxygen and energy metabolism and whether this effect has antitumoral activity in recurrent GBM. (31)P and (1)H MRSI, apparent diffusion coefficient (ADC), and high-resolution T2 and T2′ mapping (indirect marker of oxygen extraction) were investigated in 16 patients with recurrent GBM at 3 Tesla before and 1.5–2 months after initiation of therapy with bevacizumab. Changes of metabolite concentrations and of the quantitative values in the tumor and normal appearing brain tissue were calculated. The Wilcoxon signed-ranks test was used to evaluate differences for tumor/edema versus control as well as changes before versus after commencement of therapy. Survival analyses were performed for significant parameters. Tumor T2′, pH, ADC, and T2 decreased significantly in patients responding to bevacizumab therapy (n = 10). Patients with at least 25% T2′ decrease during treatment showed longer progression-free and overall survival durations. Levels of high-energy metabolites were lower at baseline; these persisted under therapy. Glycerophosphoethanolamine as catabolic phospholipid metabolite increased in responders. The MRSI data support the hypothesis that bevacizumab induces relative tumor hypoxia (T2′ decrease) and affects energy homeostasis in recurrent GBM, suggesting that bevacizumab impairs vascular function. The antiangiogenic effect of bevacizumab is predictive of better outcome and seems to induce antitumoral activity in the responding GBMs.